Antimicrobial activity of Pycnarrhena cauliflora (Miers.) Diels. methanol extract - Eti Nurwening Sholikhah; Maulina Diah; Mustofa; Masriani; Susi Iravati; Samekto Wibowo (Indonesian Journal of Pharmacology and Therapy, 2021)
Pycnarrhena cauliflora (Miers.) Diels., local name sengkubak, is one of indigenous plants from West Kalimantan that has been used as natural flavor. Pycnorrhena cauliflora is one of species of Menispermaceae family which is rich in bisbenzylisoquinoline alkaloids. This alkaloids are known to have various biological activities including antiprotozoal, antiplasmodial, antifungal and antibacterial activities. This study aimed to investigate antimicrobial activity of the P. cauliflora (Miers.) Diels. methanolic extracts against gram-positive and gram-negative bacteria. The methanolic extract of P. cauliflora (Miers.) Diels., root, leaf and stem were prepared by maceration. The disk-diffusion method was then used to determine the antimicrobial activity of the extracts against Streptococcus pyogenes, S. mutants, Staphylococcus aureus, S. epidermidis, Salmonella typhi, Shigella flexneri, Pseudomonas aeruginosa and Escherichia coli after 18-24 h incubation at 37 oC. Amoxicillin was used as positive control for gram-positive bacteria and ciprofloxacin was used as gram-negative bacteria. The inhibition zones were then measured in mm. Analysis were conducted in duplicates. The results showed in general the methanolic extracts of P. cauliflora (Miers.) Diels. root (inhibition zone diameter= 10-23 mm) were more active than that leaf (0-15 mm) and stem (0-17 mm) extracts against gram-positive bacteria. The zone inhibition diameter of amoxicillin as positive control was 8-42 mm. In addition, the methanolic extracts of P. cauliflora (Miers.) Diels. root (12-17 mm) were also more active than that leaf (0-12 mm) and stem (0-12 mm) extracts against gram-negative bacteria. The zone inhibition diameter of ciprofloxacin as positive control was 33-36 mm. In conclusion, the methanolic extract of P. caulifloria (Miers.) Diels. root is the most extract active against both gram-positive and gram-negative bacteria. Further study will be focused to isolate active compounds in the methanolic extract of the root.